Effect of Various Antiplatelet Agents on Acute Arterial Thrombosis in the Rat - Bernat, A; Mares, A M; Defreyn, G; Maffrand, J P; Herbert, J M (Thrombosis and Haemostasis, 1993)
Electrical stimulation of the rat carotid artery causes a deep medial injury and the formation of a platelet-rich thrombus.Occlusive thrombosis at sites of vessel wall injury was significantly reduced after the oral administration of clopidogrel, a potent analogue of ticlopidine, which showed dose-dependent inhibition of the thrombus formation (ED50 = 1.0 ±0.2 mg/kg, p.o.). Accumulation of thrombotic material was also considerably reduced after the i. v. administration of SR 27417, a highly potent and selective platelet activating factor receptor antagonist (ED50 = μg/kg, i.v.), nafagrel, a thromboxane A2 synthetase inhibitor (ED50 = 1.3 mg/kg, i.v.) and hirudin (ED50 = 140 μg/ kg, i.v.). A high dose (20 mg/kg, i.v.) of the anti-adhesive tetrapeptide Arg-Gly-Asp-Ser (RGDS) showed only a slight effect on thrombus formation whereas aspirin was ineffective.These results confirm that ADP and thromboxane A2 play key roles in the initiation and progression of arterial thrombus formation and suggest that platelet activating factor may also modulate thrombosis in this experimental model.